THE IMPORTANCE OF THE INCENTIVE METHOD IN ACHIEVING ACMELOGICAL DEVELOPMENT IN EDUCATION - D. X. Akhmedova (The Conference Hub, 2025)
Acmeology studies the factors, conditions, and mechanisms that ensure reaching the highest peak of personal and professional development. With the development of acmeology as a discipline, contemporary methodological issues, principles, and research strategies have become pressing topics. This article addresses the main current problems of acmeology, its subject, and methodological principles, as well as the significance of the incentive method in helping students achieve micro-acmes in the educational process.
Keywords: Acmeology, development, intellect, acme, self-improvement, motivation, incentive, intrinsic motivation.